On Death and Disability: Reframing Educators' Perceptions of Parental Response to Disability - Allred, Keith; Hancock, Christine (Disability Studies Quarterly, 2012)
Keywords: parental response to disability; stage model; grief; parent-teacher collaboration; values-based practice; strength-based approach This expository article critically reviews the literature from 1950-2010 regarding educators' perceptions of parental response to disability. Pre-service, practitioner, and professional literature are examined to explore the views presented to teacher candidates during the process of professional induction. As this literature relies upon the stage model of grief associated with Kübler-Ross' (1969) description of the acceptance of death, the effects on parent-professional relations and cultural understandings of disability are critiqued. The paper presents an alternative framing of parental response to disability emerging through positive psychology. Recommendations, based upon a disability studies in education perspective, are made regarding changes in the teacher induction process in the United States and how values-based practices informed by the emancipatory orientation of positive psychology can lead to more effective collaboration between educators and parents.